Diseño de un sistema de coordinación de procesos del área contable, financiera y administrativa para la empresa AVESCA C.A - López Pérez, Susan Johanna (2014)
With the present investigation is try to make a design of system of coordination of processes of the Countable, Financial and Administrative area of the AVESCA, Company using the provided information by the departments involved in the investigation. It´s must to bear in mind that a System of Coordination is am effective element, the same that allows to shape information of clear and specify way, getting to become in a tool that guides and provides the internal communication in each department, this will help have come presenting in the company, the same that they have caused that is not fulfilled the goals and objectives established in a short and long term.